2016
DOI: 10.1016/j.aogh.2016.04.436
|View full text |Cite
|
Sign up to set email alerts
|

Population based survey of chronic non-communicable diseases in Dubti and Asayita towns of Afar region, Northeastern Ethiopia

Abstract: Hospital (MCHH), a small urban hospital in Kumasi, Ghana, were enrolled in the study. Oral consent was obtained and the study was approved by Komfo Anokye Teaching Hospital and the Ethics Committee of the University of Chicago. The time each woman remained in the hospital determined if she was assigned to the early discharge group (<8 hours) or normal discharge group (>8 hours). Information on the pregnancy, delivery and the health of the newborn was recorded at birth. Additional health information was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Ten studies reported on the prevalence of DM ( Supplementary Table 1 ). Regional distribution of these studies included four studies from Amhara ( 16 , 27 , 30 ), two studies from Oromia ( 28 , 44 ), one study from Tigray ( 43 ), two studies from Southern Nation, Nationalities and Peoples' regional states ( 14 , 29 ) and one study from Afar ( 42 ). Using the random effect model, the pooled prevalence of DM was 5% with 95% CI (4–7%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies reported on the prevalence of DM ( Supplementary Table 1 ). Regional distribution of these studies included four studies from Amhara ( 16 , 27 , 30 ), two studies from Oromia ( 28 , 44 ), one study from Tigray ( 43 ), two studies from Southern Nation, Nationalities and Peoples' regional states ( 14 , 29 ) and one study from Afar ( 42 ). Using the random effect model, the pooled prevalence of DM was 5% with 95% CI (4–7%).…”
Section: Resultsmentioning
confidence: 99%
“…Study quality scores ranged from four to ten stars. Out of the 22 studies, 11 studies scored ten out of ten ( 10 , 16 , 27 35 ), four studies scored nine out of ten ( 9 , 36 38 ), two studies scored eight out of ten ( 14 , 39 ), two studies scored seven out of ten ( 40 , 41 ), two studies scored six out of ten ( 42 , 43 ) and one scored four out of ten ( 44 ). The major quality issues for the study that scored four out of 10 included not reporting non-response, not describing data collection tools, not controlling for confounding, inadequate statistical testing, and unjustified small sample sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Seven studies reported on the magnitude of overweight [50,51,54,57,75,82,88] (Figure 4 and Supplementary Table S2). The pooled prevalence of overweight was 20% [95% CI 14.0−25%).…”
Section: Overweightmentioning
confidence: 99%
“…The first study was conducted in an urban centre in Dire Dawa [66], and the second was conducted in a demographic and health surveillance site (Gilgel Gibe) which comprised both urban and rural areas [87]. Another study conducted from 2008 to 2009 found that 18% of participants (n = 548) were physically inactive [88]. This study was conducted in an urban environment in the Afar regional state.…”
Section: Physical Inactivitymentioning
confidence: 99%
See 1 more Smart Citation